2D density model of the Chinese continental lithosphere along a NW-SE transect - ŠIMONOVÁ, Barbora; BIELIK, Miroslav; DÉREROVÁ, Jana (Contributions to Geophysics and Geodesy, 2015)
This paper presents a 2D density model along a transect from NW to SE China. The model was first constructed by the transformation of seismic velocity to density, revealed by previous deep seismic soundings (DSS) investigations in China. Then, the 2D density model was updated using the GM-SYS software by fitting the computed to the observed gravity data. Based on the density distribution of anomalous layers we divided the Chinese continental crust along the transect into three regions: north-western, central and south-eastern. The first one includes the Junggar Basin, Tianshan and Tarim Basin. The second part consists of the Qilian Orogen, the Qaidam Basin and the Songpan Ganzi Basin. The third region is represented by the Yangtze and the Cathaysia blocks. The low velocity body (vp = 5.2 – 6.2 km/s) at the junction of the North-western and Central parts at a depth between 21 – 31 km, which was discovered out by DSS, was also confirmed by our 2D density modelling.